Effect of grafting on cucumber production and reproduction of meloidogyne javanica and m. incognita - Salata, Ariane C. [UNESP]; Bertolini, Erick Vinicius [UNESP]; Magro, Felipe O. [UNESP]; Cardoso, Antonio I.I. [UNESP]; Wilcken, Silvia Renata S. [UNESP] (FapUNIFESP (SciELO), 2012)
Grafting on resistant rootstock is a technique often recommended for cucumber crop in root-knot nematodes infested areas. We studied the yield of grafted cucumber on two rootstocks compared with non grafted in soil infested with Meloidogyne javanica or with M. incognita race 2. Nine treatments (factorial 3x3: Japanese cucumber hybrid Tsuyataro without grafting, grafted on squash hybrid Shelper and grafted on squash hybrid Excitte Ikki x without nematode inoculation, inoculated with M. incognita and inoculated with M. javanica) were evaluated in a randomized block design, with four replications and six plants per plot. There was no interaction between factors for yield evaluated characteristics (total and marketable fruit number per plant, total and marketable fruit weight per plant). Higher fruit yield was obtained in cucumber grafted on 'Shelper', for both nematode species, while cucumber grafted on 'Excitte Ikki' did not differ from non grafted plants for total fruit weight. Both nematode species reduced fruit yield, which was more evident when M. javanica was inoculated. Grafted and non grafted plants were susceptible, because they enabled the multiplication of nematodes, with a reproduction factor, at 72 days after inoculation, ranging from 3.57 to 15.04, with the highest value in cucumber non grafted inoculated with M. javanica.
Enxertia e sua influencia na produção de pepino e reprodução de meloidogyne javanica e m. incognita
Keywords: Cucumis sativus; Cucurbita spp.; Grafting; Nematodes